2005
DOI: 10.1093/molehr/gah230
|View full text |Cite
|
Sign up to set email alerts
|

IVF results in de novo DNA methylation and histone methylation at an Igf2-H19 imprinting epigenetic switch

Abstract: Recent studies suggest that IVF and assisted reproduction technologies (ART) may result in abnormal genomic imprinting, leading to an increased frequency of Angelman syndrome (AS) and Beckwith-Weidemann syndrome (BWS) in IVF children. To learn how ART might alter the epigenome, we examined morulas and blastocysts derived from C57BL/6J X M. spretus F1 mice conceived in vivo and in vitro and determined the allelic expression of four imprinted genes: Igf2, H19, Cdkn1c and Slc221L. IVF-derived mouse embryos that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(101 citation statements)
references
References 49 publications
8
89
2
2
Order By: Relevance
“…Several recent papers indicate that the DNA methylation profile is dramatically altered in the spermatozoa of infertile men [35][36][37]. Moreover, we already know that the incidence of imprinting defects such as Angelman syndrome (AS) and Beckwith-Weidemann syndrome (BWS) is elevated in children born as a result of assisted conception [38]. Assessment of such factors is likely to be a key issue for the 6th edition of the WHO manual as we move the consideration of normal sperm function beyond the traditional realms of 'fertilizing potential' and into the factors responsible for the initiation of normal embryonic development.…”
Section: The Futurementioning
confidence: 99%
“…Several recent papers indicate that the DNA methylation profile is dramatically altered in the spermatozoa of infertile men [35][36][37]. Moreover, we already know that the incidence of imprinting defects such as Angelman syndrome (AS) and Beckwith-Weidemann syndrome (BWS) is elevated in children born as a result of assisted conception [38]. Assessment of such factors is likely to be a key issue for the 6th edition of the WHO manual as we move the consideration of normal sperm function beyond the traditional realms of 'fertilizing potential' and into the factors responsible for the initiation of normal embryonic development.…”
Section: The Futurementioning
confidence: 99%
“…There is some commonality in imprinted genes among mice, cattle, and humans, and mice have been used as a model to study aberrant imprinting [31]. Li et al 2005 [32] used inbred mice to create a model in which allele specific changes in DNA and histone methylation could be followed. Crossing two species of inbred mice to create an F1 hybrid with polymorphisms in imprinted alleles allowed parental alleles to be distinguished, making it possible to observe allele specific changes in DNA and histone methylation, and for examining the mechanisms by which ART may affect phenotype.…”
Section: Use Of the Mouse To Understand Gene Function And Regulation mentioning
confidence: 99%
“…The effect of in vitro fertilization (IVF) on DNA methylation in mouse embryos has been demonstrated in many studies (5,(7)(8)(9). Small epidemiology studies in humans have suggested a 4-to 9-fold increased incidence of BeckwithWiedemann syndrome (BWS) among children conceived by IVF or intracytoplasmic sperm injection (ICSI) (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%